Elbrus - chronology, recreation - Sergii Bershov; Andriy Kiyko (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to conduct research of the historical and geographical factors of becoming and development of the Elbrus region as a center of tourism and mountaineering, to consider the use of mountain and natural complexes for active rest, to give a recreational assessment of the use of mountain natural complexes. Material & Methods: analysis of literature sources, analysis of documents, organizational analysis. Results: the historical and geographical analysis of the mountain-natural territory of the Elbrus region is carried out, the recreational assessment of the use of mountain natural complexes for active recreation is displed. Conclusions: analysis of the spatial assessment of the recreational and tourism-mountaineering potential of mountain natural territorial systems, allows choosing the safest and most attractive routes and classifying them according to complexity and safety.